A Review Paper on Application of Critical Pedagogy to Music Teaching and Learning (International Journal of Innovative Research in Engineering & Management, 2021)
Children frequently perform, produce,  listen to, and analyze music as part of their music education  in American schools. While this may provide kids a  fundamental understanding of music, we may not be  reaching them in the way that we want. Analytical  education is not a traditional music-teaching technique  since it combines philosopher with education, practise.  There are no particular teaching methods or specified body  of musical material that In the lecture, pupils must hear or  execute, unlike Orff, Kodály, or Dalcroze. There are no  mandatory resources, such as instruments or tennis balls,  and there is no set scope or order. Serious pedagogy, on the  other hand, is a way of understanding through, organizing,  and altering the links between classroom teaching,  knowledge creation, educational organizational structures,  and the greater neighborhood, culture, and national  government's social and economic interactions.
Keywords: Critical Pedagogy; Ethnic Variation; Learner’s Skill